2021
DOI: 10.4236/jbm.2021.99006
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Characteristics, Chromatographic Profiles and Inhibition of Peroxidase Activity of the Leaves of <i>Manihot esculenta</i> and <i>Manihot glaziovii</i>, Consumed as Traditional Vegetables

Abstract: Methanolic extracts from the leaves of Manihot esculenta (Two cultivars) and Manihot glaziovii, consumed as traditional vegetables in DR. Congo was chemically characterized by Thin layer Chromatography and High Performance Liquid Chromatography. In vitro biochemical activities of extracts against Radical Oxidative Species (ROS) production were assessed in cellular models, on enzymes, Myeloperoxidase (MPO) and Horseradish Peroxidase (HRP) involved in inflammation. The microscopic analysis of the powder of leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The high antioxidant activity of extracts of cassava peels and sweet potato leaves is in accordance with the results of research conducted by Lateef et al [22] and Zhang et al [65], who found that the two plant extracts showed high antiradical activity. However, the antioxidant abilities of cassava leaves, ceara rubber leaves, Chinese Albizia leaves, and lophatheri leaves, while still lower than the previous studies, were found to have high antioxidant activity [12,24,27,66]. Differences between the present study results and those reported in the literature can be due to variations in the concentration and type of solvent, extraction method, amount of total polyphenol and total flavonoid content, environmental factors, and treatment during plant growth [67][68][69][70].…”
Section: Antioxidant Activitymentioning
confidence: 64%
See 1 more Smart Citation
“…The high antioxidant activity of extracts of cassava peels and sweet potato leaves is in accordance with the results of research conducted by Lateef et al [22] and Zhang et al [65], who found that the two plant extracts showed high antiradical activity. However, the antioxidant abilities of cassava leaves, ceara rubber leaves, Chinese Albizia leaves, and lophatheri leaves, while still lower than the previous studies, were found to have high antioxidant activity [12,24,27,66]. Differences between the present study results and those reported in the literature can be due to variations in the concentration and type of solvent, extraction method, amount of total polyphenol and total flavonoid content, environmental factors, and treatment during plant growth [67][68][69][70].…”
Section: Antioxidant Activitymentioning
confidence: 64%
“…Cassava has high antioxidant activity and can inhibit Staphylococcus epidermidis and Propionibacterium acnes [22,23]. Ceara rubber has high antioxidant activity [24], and sweet potato has high antioxidant activity and can inhibit the growth of Streptococcus spp. and Staphylococcus aureus [8,25,26].…”
Section: Introductionmentioning
confidence: 99%